Continuous Quality Improvement for Calculus Using Mentor-Mentee Approach - Abdul Karim Samsul Ariffin; Hasni Mohd Mughti; Zainuddin Nooraini (SHS Web of Conferences, 2018)
This paper proposes mentor-mentee event as a method to improve the performance of the students in Calculus subject for Foundation Third Semester in Universiti Teknologi PETRONAS (UTP). About 40 mentees are selected based on their course work (CW) marks and 20 mentors are chosen from UTP undergraduate students (UG). All the mentees must complete 12 hours within two-days event. In this event, active learning (AL) and cooperative learning (CL) are utilized as a learning method, this includes brainstorming, think pair share, think problem solving (TPS), pair work, turn to neighbor summaries, and etcetera. All the outcomes are analyzed through statistical measurements. From the results, it indicates that, Mentor-Mentee Event has improved significantly the performance of the mentees in the final exam.